2015
DOI: 10.1088/0004-637x/809/1/44
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Cme’s Initial Parameters on the Arrival of the Associated Interplanetary Shock at Earth and the Shock Propagational Model Version 3

Abstract: Predicting the arrival times of coronal mass ejections (CMEs) and their related waves at Earth is an important aspect of space weather forecasting. The Shock Propagation Model (SPM) and its updated version (SPM2), which use the initial parameters of solar flare-Type II burst events as input, have been developed to predict the shock arrival time. This paper continues to investigate the influence of solar disturbances and their associated CMEs on the corresponding interplanetary (IP) shock's arrival at Earth. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Finally, it should be noted that there are also various forms of empirical forecasting methods that rely on relationships between CME-driven shocks and CMEs, CME-associated flares, or type II radio bursts. Analytical models also exit as well as hybrid approaches that combine components of empirical and analytical models (e.g., Feng and Zhao 2006;Zhao and Dryer 2014;Zhao and Feng 2015;Zhao et al 2016, and references therein).…”
Section: Physics-based Kinematic Modelsmentioning
confidence: 99%
“…Finally, it should be noted that there are also various forms of empirical forecasting methods that rely on relationships between CME-driven shocks and CMEs, CME-associated flares, or type II radio bursts. Analytical models also exit as well as hybrid approaches that combine components of empirical and analytical models (e.g., Feng and Zhao 2006;Zhao and Dryer 2014;Zhao and Feng 2015;Zhao et al 2016, and references therein).…”
Section: Physics-based Kinematic Modelsmentioning
confidence: 99%
“…These studies assume the type II sources are carried outwards by the shock along a certain direction, and infer the shock speed with a prescribed coronal density model. On this basis, several space weather forecasting schemes are constructed (Smith & Dryer 1990, Fry et al 2001, Zhao & Feng 2015. Here we show that the type II sources along a single band can move from the flank side to the top front, thus a single density model is not applicable to this kind of event.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…Similar to the ENLIL model, these models can predict if the shock arrives at Earth or not. Zhao and Feng [2015] reported on the results of their updated version of the Shock Propagation Model (SPM3). They found that the MAE of the shock travel times predicted by the SPM3 is 9.1 h. They also compared the SMP3 results with the predictions of other models such as the STOA [Dryer and Smart, 1984;Smart and Shea, 1985] model, the ISPM [Smith and Dryer, 1990], and the HAFv.2 [Fry et al, 2001] model and also with the earlier version of their own model called SMP2 (see their Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A major distinction between the models is that they describe the background solar wind through which the shock propagates at different levels of detail. Zhao and Feng [] have developed a version of the SMP model that includes also the CME speed and provided the most recent comparison between the different versions of the four shock propagation models. They found that the MAEs of the shock arrival time were in the range of 8.9–10.0 h.…”
Section: Introductionmentioning
confidence: 99%